DUAL KOTHE-TOEPLITZ UNTUK RUANG BARISAN VEKTOR - Mizan Ahmad (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2023)
In this paper, we discuss about some classes of vector sequence spaceson w(R^n). We observe their completeness and the relationships between them. At the end of this paper, we construct the Kothe-Toeplitz dual of some vector sequence spaces.